Retrocerebellar arachnoid cyst of the posterior fossa presenting with headache - Reddy Ravikanth (BLDE University Journal of Health Sciences, 2019)
Arachnoid cysts are benign, fluid-filled, cyst-liked malformations related to the arachnoid mater. Arachnoid cysts involving the posterior fossa are less common and exert local mass effect resulting in the symptoms and signs of cerebellar and brainstem dysfunction. Here, we present a case of a 14-year-old female with a retrocerebellar arachnoid cyst.